2008
DOI: 10.1007/s00128-008-9374-0
|View full text |Cite
|
Sign up to set email alerts
|

Contaminant Levels in Rainbow Trout, Oncorhynchus mykiss, and their Diets from Missouri Coldwater Hatcheries

Abstract: Organochlorine and metal contaminants often occur in commercial fish diets and can accumulate in fish to levels of concern for human consumption. Contaminant levels were investigated in diet and rainbow trout fillets from Missouri coldwater hatcheries used in "put and take" fisheries. The average fillet:diet ratio was <0.1 for lead and cadmium, 0.4-0.6 for organochlorine compounds, and about 0.8 for mercury. Trout fillet concentrations for all contaminants were low (<50 ng/g) and below Missouri's fish consumpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…The feed used in intensive and semi-intensive fish farmers contains both Cd (about 440 ng/g) and Pb (about 650 ng/g). These values, however, are similar to those found in other feed pellets commonly used in aquaculture (McKee et al 2008). Pb level in the different tissues demonstrates that in these fish foodborne Pb is poorly absorbed, as previously described for other fish species used in aquaculture (Ciardullo et al 2008).…”
Section: Discussionsupporting
confidence: 68%
“…The feed used in intensive and semi-intensive fish farmers contains both Cd (about 440 ng/g) and Pb (about 650 ng/g). These values, however, are similar to those found in other feed pellets commonly used in aquaculture (McKee et al 2008). Pb level in the different tissues demonstrates that in these fish foodborne Pb is poorly absorbed, as previously described for other fish species used in aquaculture (Ciardullo et al 2008).…”
Section: Discussionsupporting
confidence: 68%
“…A similar correlation was observed in the fat of fish meat from producers 3, 4, and 5, who used the same feed, which differed from the feed used by producers 1, 2, and 6. Other studies also confirmed the influence of the type of the feed on the content of tested compounds (10).…”
Section: Discussionmentioning
confidence: 56%
“…Fish meal and fish oil make up around 50-70% of all ingredients in fish feed. Previous studies (e.g., Easton et al 2002;Antunes and Gil, 2004;Hites et al 2004;Navas et al 2005;Bordajandi et al 2006;Maule et al 2007;Kelly et al 2007;McKee et al 2008;Serrano et al 2008;Shaw et al 2008;Botaro et al 2011;Grigorakis &Rigos, 2011) found amounts of DDT, PCBs, and PBDEs in Atlantic salmon diets of 36.66, 10.9, and 36.66 ng g-1, respectively, in their Mediterranean mariculture investigation. These undesired contaminants in farmed high energy Atlantic salmon were caused by fish oils from contaminated pelagic fish species used as a feed element in salmonid diets (Berntssen et al 2016).…”
Section: Introductionmentioning
confidence: 89%